The dynamic tumor extracellular matrix: Biophysical cues, cellular crosstalk, and disease progression - Joshi, Omkar; Hamidi, Hellyeh; Mathieu, Mathilde; Ivaska, Johanna (Elsevier BV, 2026)
The interplay between diverse cell types and their extracellular matrix (ECM) is fundamental for multicellular life. The ECM is a complex meshwork of fibrillar proteins and soluble factors. Cells and their surrounding ECM interact bidirectionally, whereby cells deposit their tissue-specific ECM and remodel it enzymatically and by exerting contractile forces. The ECM in turn modulates cellular functions like gene expression, proliferation, and motility. A careful balance of this interaction is key for homeostasis, and is lost during cancer progression. Different cell types constituting a tumor including cancer and stromal cells, contribute to an imbalanced cell-ECM crosstalk within the tumor. Cumulatively, this leads to a tumor ECM characterized by particular features like increased stiffness and viscoelasticity, altered alignment, bundled fibers, etc. In this review, we discuss the advances in our understanding of the tumor ECM architecture and the multicellular interactions that help achieve it, with a special focus on increasing granularity in disentangling the contributions of individual tumor ECM features in disease progression.